Impact of Oscillator Noise in Bistatic and Multistatic SAR - Krieger, Gerhard; Younis, Marwan (IEEE Geoscience and Remote Sensing Letters, 2006)
This letter addresses the impact of limited oscillator stability in bistatic and multistatic synthetic aperture radars (SARs). Oscillator noise deserves special attention in distributed SAR systems since there is no cancellation of low-frequency phase errors as in a monostatic SAR, where the same oscillator signal is used for modulation and demodulation. It is shown that the uncompensated phase noise may cause a time-variant shift, spurious sidelobes, and a broadening of the impulse response, as well as a low-frequency phase modulation of the focused SAR signal. Quantitative estimates are derived analytically for each of these errors based on a system-theoretic model taking into account the second-order statistics of the oscillator phase noise. © 2006 IEEE.
DLR Import::2019-04-02
Keywords: Bistatic radar; Interferometry; Multistatic radar; Oscillator; Phase noise; Synchronization; Synthetic aperture radar